2020
DOI: 10.1016/j.ygyno.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

GOG 244-The lymphedema and gynecologic cancer (LEG) study: Incidence and risk factors in newly diagnosed patients

Abstract: Objectives: To evaluate the incidence and risk factors for lymphedema associated with surgery for gynecologic malignancies on GOG study 244.Methods: Women undergoing a lymph node dissection for endometrial, cervical, or vulvar cancer were eligible for enrollment. Leg volume was calculated from measurements at 10-cm intervals starting 10 cm above the bottom of the heel to the inguinal crease. Measurements were obtained preoperatively and postoperatively at 4-6 weeks, and at 3-, 6-, 9-, 12-, 18-, and 24months. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 35 publications
0
45
1
Order By: Relevance
“…Risk factors can include radiation, large radiation field, conventional fractionation radiation, obesity, age, chemotherapy infusion to the affected limb, taxane-based chemotherapy, advanced stage disease, number of lymph nodes removed, and number of positive lymph nodes. [2,[4][5][6][7][8][9][10][11] Secondary lymphedema can also result from traumatic injury or infections involving the lymphatic tree. Less frequently, secondary lymphedema can develop in patients due to extreme obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors can include radiation, large radiation field, conventional fractionation radiation, obesity, age, chemotherapy infusion to the affected limb, taxane-based chemotherapy, advanced stage disease, number of lymph nodes removed, and number of positive lymph nodes. [2,[4][5][6][7][8][9][10][11] Secondary lymphedema can also result from traumatic injury or infections involving the lymphatic tree. Less frequently, secondary lymphedema can develop in patients due to extreme obesity.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Comprehensive lymphadenectomy can result in significant chronic long-term leg edema impairing patients' quality of life. [7][8][9] Efforts has been made to limit the extent of nodal dissection to minimize longterm lymphedema side effects by the application of sentinel lymph node (SLN) mapping algorithm with success. 10 SLN mapping had been validated as an alternative to full lymphadenectomy without compromising diagnostic accuracy especially in low grade clinical stage 1 endometrial cancer where the chance of nodal metastasis is commonly reported to be less than 11,12 10%.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of LLL after standard surgical treatment, including PLND, of cervical cancer varies broadly in the literature, in the range of 3–62% [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 25 , 26 , 31 ]. Such great variation is likely attributed to the flaws in LLL assessment, such as the absence of objective assessment methods, the simple postoperative assessment instead of longitudinal repeated follow-up, as well as a short period between the surgery and endpoint assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Out of ten identified prospective studies, the description of LLL assessment methodology is only vaguely portrayed in two [ 43 , 44 ]; three studies were based on subjective reports [ 45 , 46 , 47 ]; and only two were based on objective diagnostic methods (bioimpedance spectroscopy, CT, or MRI) [ 25 , 48 ]. The last three prospective studies utilized objective assessment using circumferential measurements [ 7 , 10 , 19 ]. In the first study, 34.8% (48/138) of patients developed LLL during the two years of follow-up [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation